PEMBELAJARAN DARING DI MASA COVID-19 TERHADAP MINAT BELAJAR MAHASISWA INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Mulia Rasyidi (LPPM Institut Pendidikan Nusantara Global, 2021)
The type of research used follows the type of qualitative research. Qualitative research is known to be descriptive in nature which in its application uses qualitative data analysis which makes data explanations in the form of information that is easy to understand. The learning that is assumed to be used as the subject is at the Global Nusantara Education Institute in this study using an online learning model or what is often referred to as distance learning. Students conduct online learning and interact in learning with lecturers using several applications that are often used in general, such as Google Meet, Google Classroom, Zoom, and Whatsapp Group which are independently created by students. This study aims to determine the influence of online learning on student interest in learning during the COVID-19 period at the Global Nusantara Education Institute. Respondents taken in this study were students and lecturers at the Global Nusantara Institute of Education. The results obtained in the study showed that online learning during the COVID-19 pandemic affected student interest in learning, students felt bored during learning because they did not meet or meet face-to-face with friends and lecturers directly on campus.